A quest for understanding: older migrants’ wellbeing beyond integration in Sweden - Zhou, Anna; Ranada, Åsa Larsson; Roos, Susanne; Hellström, Ingrid (Frontiers in Public Health, 2025)
PurposeThis study investigates how older foreign-born adults in Sweden experience and navigate social connectedness as a determinant of wellbeing.MethodsEmploying Glaser’s grounded theory methodology, we collected qualitative data through individual (n = 1) and focus group (n = 5) interviews with 23 participants aged 60 + representing four distinct cultural-linguistic groups: Arabic, Finnish, Spanish, and Chinese speakers.ResultsThe analysis identified “a quest for understanding” as the core category, encompassing three dimensions: (1) wanting to be understood, (2) wanting to understand, and (3) reaching for reconciliation. While participants shared universal needs for validation and connection, their experiences revealed tensions between aspirations and the challenges of language barriers, cultural distance, and generational differences. Notably, perceptions and experiences showed strong within-group similarities but significant between-group variations.DiscussionFramed by Nordenfelt’s concept of wellbeing as “want-equilibrium,” the findings highlight understanding as both a social need and existential pursuit. While Finnish speakers’ minority status eased integration, Arabic and Chinese speakers navigated systemic inclusion yet social exclusion. Resilience strategies—bicultural fluency, insular solidarity, or self-reliance—reflected Bourdieusian capital disparities. Wellbeing thus hinges on mutual recognition: migrants’ adaptability and Sweden’s capacity to perceive them beyond structural categories.